Ion exchange behavior of polyaniline and polyaniline/ silica composite / Amirah Amalina Ahmad Tarmizi and Muhammad Adam 'Azmi - Ahmad Tarmizi, Amirah Amalina; 'Azmi, Muhammad Adam (UiTM Press and Research Management Centre Universiti Teknologi MARA, 2020)
This study was conducted to compare the ion exchange behaviour of polyaniline (PANI) and polyaniline/silica (PANI/silica) composite. Rice husk silica (SiRH) was obtained from the combustion of rice husk ash followed by acid digestion method using sulfuric acid. Next, pristine PANI was synthesized via in situ oxidative polymerisation method using aniline and potassium dichromate in the acidic medium. Composite of PANI/SiRH was prepared with a similar method with the addition of SiRH in the process. Characterisations were done by employing X-Ray diffractometry and Fourier transform infrared spectroscopy. Polyaniline and PANI/SiRH composite were mixed with a solution containing Na+, Mg2+, and K+. The concentrations of metal ions before and after contact with PANI and PANI/SiRH were measured using inductively coupled plasma-optical emission spectroscopy (ICP-OES). The effect of SiRH composition, contact time and pH on the ion exchange behaviour of PANI and PANI/SiRH composite was investigated. Results revealed that higher SiRH content in PANI/SiRH shows better ion-exchange properties with the optimum contact time of 30 minutes. The pH value of the metal ions decreased throughout the experiment.